Isolation of Pyran Composition and Anti-Parkinson’s Activity of euphorbia Cyathophora - Ruby, S; Jaykar, B (Asian Journal of Pharmaceutical Research and Development, 2019)
Aim of the study: The aim of this research was to investigate the phytochemical profile, isolate the phytoconsitutuents, Characterised and evaluation of Anti Parkinson activity of ethanolic extract of Indian Medicinal plant of E.cyathophora Materials and methods: Qualitative phytochemical analysis for their phyto constituents. Ethanol was used to extract the crude bio active compound from whole E. Cyathophora plant. Phenolic derivative were isolated from the ethanolic extract of E. cyathophora by using suitable solvent system and characterised by IR, NMR, MASS spectrophotometric method. The total Neuroprotective activities of E. Cyathophora extract were measured by haloperidol induced experimental animal models. Result: Qualitative phytochemical analysis showed phenolic compounds, Flavonoids, Alkaloids, glycosides, phenolic compounds and Tannins were in high amounts. The isolated compound Phenolic derivative showed various regions from IR, NMR and MASS the functional groups, mass of the molecule and proton were analysed and confirmed. The effects of E. Cyathophora (200, 400mg/kg, p.o) were studied using in vivo behavioural parameters like catalepsy, muscle rigidity and locomotor activity and its effects on neurochemical parameters in rats. The increased haloperidol-induced cataleptic scores were significantly(p<0.01) found to be reduced, with EEEC at dose of 200mg/kg and 400mg/kg(ip). EEEC administration showed significant increase in dopamine level and significant reduced in serotonin and L-glutamate level. Daily administration of EEEC (400mg/kg) significantly improved motor performance. Conclusion: Overall results the study proved that E. Cyathophora possessed potential components involving in anti -Parkinson treatment significantly attenuated the motor defects and also increased the neuro chemical dopamine level. Keywords: E. cyathophora, Anti-Parkinson‟s activity, Ethanol extract, L-Dopa, Carbidopa and Haloperidol.